2021
DOI: 10.1111/eci.13489
|View full text |Cite
|
Sign up to set email alerts
|

Stroke risk reassessment and oral anticoagulant initiation in primary care patients with atrial fibrillation: A ten‐year follow‐up

Abstract: Aim: To examine the change in stroke risk over time and determine the proportion of patients with atrial fibrillation (AF) who were initiated on an oral anticoagulant (OAC) as their stroke risk increased from low/moderate to high, using the Australian general practice data set, MedicineInsight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Further, the patient factors most strongly influencing GPs' prescribing decisions were stroke and bleeding risk, older age and history of ICH. Identifying GPs' sources of prescribing information and their decision‐making process could support efforts to improve guideline usability so that non‐guideline‐adherent OAC prescribing and inconsistent thromboprophylaxis in AF is reduced in Australian general practice 11,12 . Saying this, we acknowledge that prescribers may appropriately deviate from guideline‐recommended therapy in the interests of person‐centred care, because of individual clinical contexts and the patients' goals of therapy 16,26 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Further, the patient factors most strongly influencing GPs' prescribing decisions were stroke and bleeding risk, older age and history of ICH. Identifying GPs' sources of prescribing information and their decision‐making process could support efforts to improve guideline usability so that non‐guideline‐adherent OAC prescribing and inconsistent thromboprophylaxis in AF is reduced in Australian general practice 11,12 . Saying this, we acknowledge that prescribers may appropriately deviate from guideline‐recommended therapy in the interests of person‐centred care, because of individual clinical contexts and the patients' goals of therapy 16,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from the Australian general practice setting indicated that one‐third of patients whose stroke risk changed from low‐to‐moderate to high were not prescribed OAC therapy. In the remaining patients who received OAC therapy, OAC initiation was reported to be delayed by a median of 2 years, which suggested a need for more frequent stroke risk reassessments 12 . This is also true with bleeding risk reassessments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations